THE IMPORTANCE OF ENGLISH IN VOCATIONAL EDUCATION - Obidova Gulshoda Khidirovna; Khaydarova Asal Fakhriddin qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION This article examines the importance of teaching English in the vocational education system, its close relationship with modern labor market requirements, and its role in developing professional competencies. Particular attention is paid to teaching English in vocationally oriented technical and vocational education institutions. In addition, the theoretical foundations and practical effectiveness of ESP (English for Specific Purposes) and CLIL (Content and Language Integrated Learning) approaches are analyzed as effective methods for teaching English in vocational education.